The Influence of the Implementation of E-Filling and Tax Volunteers on Taxpayer Compliance at the Pasir Pengaraian Tax Service, Counseling and Consultation Office - Nurhayati Nurhayati; Sri Yunawati (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study aims to determine the effect of the application of E-Filling and Tax Volunteers on Taxpayer Compliance at the Pasir Pengaraian Tax Service, Counseling and Consultation Office. The results of data collection showed that the returned questionnaires were 100 questionnaires. The analytical technique used in this study is multiple linear regression analysis technique which serves to determine the linear relationship between two or more variables. The results of the research on the application of e-filling are 2.301> 1.984 ttable with the results that there is a significant positive effect, between the application of efilling and taxpayer compliance, tax volunteers of 8.821 > 1.984, meaning there is a positive and significant effect between tax volunteers and taxpayer compliance . The results of the value of Fcount > Ftable (83.366> 2.70), d The results show that the application of E-Filling has an effect on taxpayer compliance because the application of E-Filling can ensure the security of taxpayer data becomes more secure.